Investigation of light intensity and temperature dependency of solar cells electric parameters - Tobnaghi, Davoud Mostafa; Madatov, Rahim; Farhadi, Payam (Видавництво Львівської політехніки, 2013)
In this paper, the performance and overview use of solar cells is expressed. The role of temperature, sunlight intensity on the solar cells electric parameters has been studied. Experimental results the amount of solar cell output parameters variations such as maximum output power, open circuit voltage, short circuit current, and fill factor in terms of temperature and light intensity shows. the most significant is the temperature dependence of the voltage which decreases with increasing temperature. Also output current of solar cells is directly proportional to the light intensity. The best performance of solar panels in sunny and cold day has been suggested. Obtained results could lead to optimal use of solar cells.
Keywords: solar cells; temperature; light intensity; open circuit voltage; short sicut current; output power